SAPHO Syndrome of the Temporomandibular Joint Associated with Sudden Deafness - Marsot-Dupuch, Kathlyn; Doyen, Jacques E.; Grauer, Walter O.; de Givry, Sebastien C. (American Journal of Neuroradiology, 1999)
Summary: We report a case of arthritis of the temporomandibular joint (TMJ) associated with sclerosing osteomyelitis of the mandible and temporal bone, causing deafness. The presence of a palmoplantar pustulosis established the diagnosis of SAPHO syndrome. SAPHO (an acronym referring to synovitis, acne, palmoplantar pustulosis, hyperostosis, and osteitis) syndrome is defined by the association of characteristic osteoarticular and dermatologic manifestations, with diffuse sclerosing osteomyelitis of the mandible being a part of this entity. We review the literature of SAPHO syndrome with mandibular manifestations and discuss the mechanisms of inflammatory spread from the TMJ to the cochlea. To our knowledge, this is the first description of skull base involvement in a patient with SAPHO syndrome leading to sudden deafness.